Menegosiasikan yang Mustahil: BATNA, Hurting Stalemate, dan Runtuhnya Perundingan Damai Turki–PKK - Intan Tiara Kartika; Zulfikar Adjie; Sanri J. Dotutinggi (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2025)
The protracted conflict between the Turkish state and the Kurdistan Workers’ Party (PKK) remains one of the most enduring ethnopolitical confrontations in modern history. Despite initiatives such as the Oslo Process and the İmralı Talks, negotiations have consistently collapsed. This study examines the roots of these failures by integrating strategic negotiation theories—particularly BATNA and the Hurting Stalemate model—with perspectives from identity politics and collective trauma. Employing qualitative, thematic analysis of secondary sources, it argues that breakdowns cannot be explained solely through material or strategic lenses. Instead, they stem from entrenched ideological discord, symbolic marginalization, and structural asymmetries of power and recognition. The Turkish state’s reliance on coercion and systemic delegitimization of the PKK has impeded equitable dialogue. Conceptually, the article advances an interdisciplinary interpretation of negotiation failures and highlights the necessity of symbolic and psychosocial dimensions. Findings affirm that recognition, narrative pluralism, and legitimacy are essential to sustainable peace.